STRATEGI BERTAHAN HIDUP PENGRAJIN PANDAI BESI DI NAGARI SUNGAI PUA KECAMATAN SUNGAI PUA KABUPATEN AGAM - Fitryani, Fauza; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted in Nagari Sungai Pua, Agam Regency, West Sumatra Province. The purpose of this research is to find out the obstacles of blacksmith craftsmen in running their business. To find out the strategies carried out by blacksmiths in maintaining their business in Nagari Sungai Pua, Sungai Pua District, Agam Regency in maintaining their livelihoods. In this study, the technique of taking subjects using purposive sampling has been used criteria in this study. The theory used in this study uses Edi Suharto's theory by looking at active, passive, and network strategies. This research uses a qualitative approach with a descriptive type. To obtain relevant research results, the researcher has conducted interviews with 6 subjects and has made direct observations to the field. The results of this study are the obstacles faced by blacksmith craftsmen and there are 3 strategies used to survive. The obstacles faced by craftsmen are the difficulty of getting equipment such as anvil stones and lack of capital. Strategies carried out by blacksmith craftsmen. The first strategy used is an active strategy by empowering the potential of the family, the second is a passive strategy by reducing work members and the third is a network strategy by utilizing the social network of fellow blacksmith craftsmen and using social media networks. Keywords: blacksmith, survival strategy, barriers